Pengaruh Metode Mind Mapping Terhadap Motivasi Belajar Siswa Pendidikan Agama Kristen kelas XI SMK Negeri 1 Siatas Barita - Devi Ani Aritonang; Oktober Tua Aritonang; Hanna Dewi Aritonang; Damayanti Nababan; Sandy Ariawan (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The purpose of this research is to determine the positive and significant influence of the Mind Mapping Method on the learning motivation of class XI Christian religious education students at SMK Negeri 1 Siatas Barita. Tony Buzan's theory suggests that the Mind Mapping Method is a learning method that uses a note-taking strategy using keywords, image symbols, sounds, shapes and feelings. The method used in this research is a quantitative research method and the type of research is pre-experimental design in the form of "One Shot Case Study". The population was all class Data was collected using a positive closed questionnaire with 30 items, namely 15 items for variable Siatas Barita: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.591 > rtable(=0.05,n=34) = 0.339. b) Testing a significant relationship obtained a value of tcount= 4.140 > ttable(=0.05,dk=n-2=32)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 34.9%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=15, dk denominator=n-2=34-2=32) namely 17.14 > 2.01. Thus Ha is accepted and H0 is rejected.